Platelet-derived extracellular vesicles induced through different activation pathways drive melanoma progression by functional and transcriptional changes - Zeynep Tavukcuoglu; Umar Butt; Alessandra V. S. Faria; Johannes Oesterreicher; Wolfgang Holnthoner; Saara Laitinen; Mari Palviainen; Pia R-M Siljander (Cell Communication and Signaling)
Abstract Background Beyond their conventional roles in hemostasis and wound healing, platelets have been shown to facilitate hematogenous metastasis by interacting with cancer cells. Depending on the activation route, platelets also generate different platelet-derived extracellular vesicles (PEVs) that may educate cancer cells in the circulation or within the tumor microenvironment. We engaged different platelet-activating receptors, including glycoprotein VI and C-type lectin-like receptor 2, to generate a spectrum of PEV types. This allowed us to investigate the differential capacity of PEVs to alter cancer hallmark functions such as proliferation, invasion, and pro-angiogenic potential using melanoma as a model. Additionally, we analyzed changes in the cell transcriptomes and cancer EV profiles. Methods Two human melanoma cell lines (MV3 and A2058) with differential metastatic potential were studied in the 3D spheroid cultures. Human platelets were activated with collagen related peptide (CRP), fucoidan from Fucus vesiculosus (FFV), thrombin & collagen co-stimulus and Ca2+ ionophore, and PEVs were isolated by size-exclusion chromatography followed by ultrafiltration. Spheroids or cells were treated with PEVs and used in functional assays of proliferation, invasion, and endothelial tube formation as well as for the analysis of cancer EV production and their tetraspanin profiles. Differentially expressed genes and enriched signaling pathways in the PEV-treated spheroids were analyzed at 6 h and 24 h by RNA sequencing. Results Among the studied PEVs, those generated by CRP and FFV exhibited the most pronounced effects on altering cancer hallmark functions. Specifically, CRP and FFV PEVs increased proliferation in both MV3 and A2058 spheroids. Distinct tetraspanin signatures of melanoma EVs were induced by all PEV types. While the PI3K-Akt and MAPK signaling pathways were activated by both CRP and FFV PEVs, they differently upregulated the immunomodulatory TGF-β and type-I interferon signaling pathways, respectively. Conclusions Our study revealed both shared and distinct, cancer-promoting functions of PEVs, which contributed to the transcriptome and metastatic capabilities of the melanoma spheroids. Inhibiting the platelet receptors that modulate the PEVs’ cancer-promoting properties may open up new strategies for identifying promising treatment targets for cancer therapy.